Geochemical data of river water and sediments from the Ganga Basin from years 2014-2016 - Soumita Boral; Indra Sekhar Sen; Aditya Tripathi; Bhupendra Sharma; Sanjukta Dhar (PANGAEA, 2020)
This dataset consists of trace-element concentration of 243 river water samples collected from 38 locations from the source of the river to its sink. It includes geochemical data of river water samples analysed for as pH, temperature, specific electrical conductivity, dissolved trace elements and heavy metals concentrations. Samples were collected from targeted locations in the Ganga Basin. Water samples were collected from 38 locations from the source to the sink of the river during the pre-monsoon (April—June), the monsoon (July—September), and the post-monsoon seasons (October—December) to capture both low and high discharge conditions. In the headwaters and the upstream segments of the river water samples were collected corresponds to 2014, 2015, and 2016, whereas the downstream samples were collected in 2016. In addition to river water samples, this dataset also contains trace element concentrations of rainwater, groundwater, snow, glacier ice, and surface sediments collected from several upstream sites. Sampling and analytical protocols are outlined by Boral et al., 2020. This dataset is the raw data provided in the main text and supplementary files of Boral et al., 2020.